The Argument from the Work between Ontological Prerequisites and Teleological Assumptions - Kouklakis, Emmanuel (Conatus - Journal of Philosophy, 2018)
This paper discusses Aristotle’s argument of the "work" or entelecheia, that is being severely challenged today. In particular, it is argued that the argument of the work is based on strong ontological and teleological assumptions, while at the same time it pressuposes a particular metaphysical biology, which today can no longer be accepted. Moreover, the argument of the work, it is claimed, presupposes a nature that defines our goals and identifies the direction ethics should follow.